2017
DOI: 10.2196/publichealth.7701
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Prevention Impact of Mother-to-Child Transmission of HIV in Concentrated Epidemics With Program and Survey Data

Abstract: BackgroundThe prevention of mother-to-child transmission (PMTCT) of HIV program was introduced in Vietnam in 2005. Despite the scaling up of PMTCT programs, the rate of mother-to-child HIV transmission in Vietnam was estimated as high as 20% in 2013.ObjectiveThe objective of this study was to assess the outcomes of PMTCT and identified factors associated with mother-to-child transmission and infant survival using survey and program data in a high HIV burden province in Vietnam.MethodsThis community-based retro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In our study, the rate of MTCT has been decreasing through time in parallel with the increased coverage of ART intervention for women during pregnancy. Similar results were observed in Thai Nguyen, Vietnam 11 and in other Asian countries. In a prospective study during 2004–2011 in eight counties in China, Wang et al 19 reported that vertical transmission of HIV declined from 11.2 to 1.2%, corresponding to an increase in ART coverage for pregnant women from 61% to 96%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, the rate of MTCT has been decreasing through time in parallel with the increased coverage of ART intervention for women during pregnancy. Similar results were observed in Thai Nguyen, Vietnam 11 and in other Asian countries. In a prospective study during 2004–2011 in eight counties in China, Wang et al 19 reported that vertical transmission of HIV declined from 11.2 to 1.2%, corresponding to an increase in ART coverage for pregnant women from 61% to 96%.…”
Section: Discussionsupporting
confidence: 89%
“…In one study conducted in Thai Nguyen, Vietnam, the authors reported that the rate of transmission decreased from 27.3% in 2008 to 6.7% in 2012. 11 The purpose of this study is to determine the evolution of the HIV transmission rate in infants from 2007 to 2018 and to identify risk factors of HIV transmission among HIV-exposed infants at one pOPC in An Giang province, Vietnam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ART coverage in pregnant women in the province increased from 18.2% in 2008 to 70% in 2011. 27 A national assessment of HIV MTCT rates among children who were diagnosed in early infancy also showed a decrease but rates remained high at 8.3% in 2012. 28 Vietnam aims to achieve an MTCT rate of less than 2% by 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Concluding that integration or linkage is possible, the authors presented an approach to align the two streams of strategic information. Linkage across health sectors is something Nguyen et al call for in their analyses of a community-based retrospective cohort study among pregnant women diagnosed with HIV infection in Vietnam [ 11 ]. To bridge serious gaps in efforts to eliminate mother-to-child transmission, the authors endorsed data linkage across HIV and maternal and child health programs.…”
mentioning
confidence: 99%